(untitled) (Research, Society and Development, 2022)
The study aimed to discuss the impact of neoliberalism impacted on the Sistema Único de Saúde (SUS) in relation to the level of health care. The methodology is a reflection study, with a descriptive qualitative approach. In the context of the studies, one can discuss the political neoliberal, which masks the right of the population that impacts labor rights to increase the margin of the private economy, overlapping the public space. The area of governmental health in the public sphere is rejected and disabled by neoliberalism, and increasingly threatened by the logic of the market, where the participation of the State, as a sponsor of health, becomes distorted and ineffective, when it transfers to civil society the responsibility to provide for the social well-being of the population. It is concluded that the studies show that it is necessary to fight for the performance of the political public, based on the constitutional commitment, which generated the SUS, for the governmental relationship, which considers health as a right for all, however, the lack of the daily population is perceived of lesser resource.